Overall Equipment Effectiveness (OEE) Through Total Productive Maintenance (TPM) Practices - A Study Across The Malaysia Industries - Kaliannan, Batumalay (2010)
This has provided the impetus to the leading organizations worldwide to adopt effective and efficient maintenance strategies such as Total Productive Maintenance (TPM), over the traditional firefighting reactive maintenance approaches. TPM employs overall equipment effectiveness (OEE) as a quantitative metric for measuring the performance of a productive system. OEE is the core metric for measuring the success of TPM implementation program. This metric has become widely accepted as a quantitative tool essential for measurement of productivity in manufacturing operations.